2011
DOI: 10.1007/s12070-011-0355-y
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized, Double-Blind Study of Coblation versus Dissection Tonsillectomy in Adult Patients

Abstract: This randomized double blind study was conducted prospectively to determine whether coblation tonsillectomy fared better than the conventional dissection method in terms of postoperative pain, bleeding, and rapidity of healing in adult Indian patients undergoing tonsillectomy. Sixty adult patients undergoing tonsillectomy for benign indications were randomized to have one tonsil removed by subcapsular radiofrequency ablation method and the other by conventional dissection method. The operative time and blood l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 25 publications
(34 reference statements)
4
25
2
Order By: Relevance
“…Additionally, because of the emetic nature of tonsillectomy, postoperative nausea and vomiting (PONV) can occur in up to 70% of patients; this may contribute to dehydration, or even disruption of the surgical site in severe cases . Therefore, many therapeutic modalities have been used as an effective means of controlling postoperative morbidities in patients . These have included preoperative medications, pre‐ or posttonsillectomy local anesthetics, variations in surgical technique, intraoperative medication, and postoperative pain‐relief medications and antiemetics.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, because of the emetic nature of tonsillectomy, postoperative nausea and vomiting (PONV) can occur in up to 70% of patients; this may contribute to dehydration, or even disruption of the surgical site in severe cases . Therefore, many therapeutic modalities have been used as an effective means of controlling postoperative morbidities in patients . These have included preoperative medications, pre‐ or posttonsillectomy local anesthetics, variations in surgical technique, intraoperative medication, and postoperative pain‐relief medications and antiemetics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the commonly prescribed acetaminophen may not be adequate for post-tonsillectomy pain relief without codeine and at higher doses it may cause hepatic toxicity (5). Therefore, there is an ongoing research on the investigation of effectiveness of many surgical and pharmacological products in post-tonsillectomy pain management (2,4,5,7,9,23,26). Subramayam et al (2) reported their own experience on the use of ATC acetaminophen, dexamethasone and ibuprofen in pain management as no increase in the incidence of inadequate pain control or serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…In control side, there was a statistically significant difference in patient pain scores in the morning compared to that of afternoon except 6th and 13th postoperative days (Table II). Results indicated that for 6 out of 14 days (at 3rd, 4th, 8th, 9 9th, 10th and 14th days), patients evaluated significantly more post-tonsillectomy pain for non-treated side in the mornings than afternoons (Figure 1). With hyaluronic acid, there was a statistically significant difference in patient pain scores in the morning compared to that of afternoon except 1th and 3rd postoperative days (Table II).…”
Section: Effectiveness Of Hyaluronic Acid On the Reduction Of Post-tomentioning
confidence: 99%
See 1 more Smart Citation
“…(12) Many literatures focused on the conventional dissection tonsillectomy operation that the healing is more rapid and postoperative pain isless than other studied techniques. (13) Tonsillectomy remains a painful operation often disruptive of family and patients life for more than a week during convalescence whatever the technique.…”
Section: Discussionmentioning
confidence: 99%